Classification and relationships of living species of Laternulidae (Bivalvia, Anomalodesmata): new light on lantern shells - Taylor, John D.; Glover, Emily A.; Williams, Suzanne T. (Zootaxa, 2026)
Species of the marine bivalve family Laternulidae are frequently misidentified with some having particularly tangled nomenclatural histories. To redress these problems all available type specimens or new images of them, totalling 52 of the 56 nominal species, were examined and assessed. Concurrently, new molecular analyses identified major clades and corroborated species boundaries based on shell characters. Two clades of laternulids were recognised as subfamilies Laternulinae and Exolaternulinae the latter introduced herein and characterised by presence of a lithodesma. A new classification of the family is presented. The depth of insertion of the pallial sinus is identified as a useful character separating species with similar shell shapes. Two new genera Cryolaternula and Parilaternula are proposed. Twenty-eight putative species are recognised with some resurrected from prior synonymy. Six new species are described: Laternula pristissinus Taylor & Glover, L. inopinata Taylor & Glover, L. omissa Taylor & Glover, Parilaternula acuta Taylor, Fukuda & Haga, P. certa Taylor & Glover and P. delicata Taylor, Glover & Hong. To stabilise the name Exolaternula a lectotype is selected for the type species, Anatina truncata Lamarck, 1818. Exolaternulinae species are distributed from the Arabian Gulf eastwards to Japan and eastern Russia and northern Australia at the southern limit. Laternulinae species occur around Australia, northern Indian Ocean, through the central Indo-W. Pacific to Japan, with Cryolaternula confined to the Southern Ocean within the Antarctic Convergence.